1997
DOI: 10.1177/00220345970760081001
|View full text |Cite
|
Sign up to set email alerts
|

Pathway for Uptake and Degradation of X-Prolyl Tripeptides in Streptococcus mutans VA-29R and Streptococcus sanguis ATCC 10556

Abstract: The growth of Streptococcus mutans and Streptococcus sanguis in the oral environment requires that these micro-organisms be able to degrade salivary proteins and to assimilate the resulting peptides as an amino nitrogen source. Our research is aimed at the definition of the proteolytic enzyme systems in these oral streptococci which allow them to utilize such substrates. In the present work, the nature of the hydrolytic activity expressed by S. mutans VA-29R and S. sanguis ATCC 10556 against X-Pro4-nitroanilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This activity has been described in studies concerning tripeptide degradation systems of S. sanguinis and S. mutans (8) and collagen degradation by S. gordonii Challis in the IE model (19). Our work presents the first biochemical and genetic studies of purified enzyme.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This activity has been described in studies concerning tripeptide degradation systems of S. sanguinis and S. mutans (8) and collagen degradation by S. gordonii Challis in the IE model (19). Our work presents the first biochemical and genetic studies of purified enzyme.…”
Section: Discussionmentioning
confidence: 86%
“…A tripeptide transport system was identified in S. sanguinis that permitted the assimilation of free amino acids by membrane-bound and intracellular proteolysis. It was further concluded that x-prolyl dipeptides were insufficient for transport (8). This is counterintuitive to the action of Sg-xPDPP that results in high concentrations of extracellular dipeptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus mutans and Streptococcus sanguinis also contain complex proteolytic pathways necessary for growth (e.g. Cowman & Baron, 1997). In contrast, supragingival plaque from macaque monkeys expresses both exoglycosidases and a wide range of proteolytic activities (Smith & Beighton, 1986.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of the amino acid is then prioritized, so the transport and metabolism of arginine-containing peptides may become particularly important. The amino acid and peptide transport systems of viridans streptococci have been described previously (2,5,10,25,31), and it has been shown that amino acids and small peptides are readily imported while those exceeding size limitations require hydrolysis by endo-and exopeptidases either present on the surface or secreted by these cells (6). One such activity that could meet the transport and metabolic challenges in vivo is an arginine aminopeptidase.…”
mentioning
confidence: 99%